Les cuticules dispersées du crétacé et du tertiaire de colombie (1970)
With the inventory of the scattered cuticles of the Cerrejón Basin (State of Guajira), the writers take up the comparison of the various cretaceous and tertiary deposits in Colombia. This first study deals with specimens gathered in the carbonaceous deposits located on the limits of the Hato Nuevo y Cerrejón formations (Upper Paleocene-Lower Eocene). The taxonomic value of the epidermical characteristics preserved due to the fossilization has led the writers to make some reserves as to the nomenclature and the systematic of the scattered cuticles.